Handling Juvenile Delinquency: The Role of the Social Welfare Service in Handling Cases in Samarinda City - Suryaningsi Suryaningsi; Marwiah Marwiah; Jawatir Pardosi; Jamil Jamil; Asnar Asnar; Edi Rahmad; Muhammad Rean Wahyudi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The purpose of this research is to examine the prevention of juvenile delinquency by the Department of Social Welfare in handling cases in Samarinda City. This type of qualitative descriptive research focuses on the empowerment and obstacles faced by the Office of Social Welfare. This research has been carried out from October to January 2022. The primary data sources are the head of the service, the head of the rehabilitation section for children and the elderly, social workers and counseling. Data collection techniques through observation, interviews, and documentation. Data analysis techniques through reduction, display and conclusion. The validity of the data using data triangulation. The results of the study, adolescent empowerment will have implications in developing the mindset of youth independence so that they have the ability to work and gain experience. Barriers: on the financial aspect, human resources, shelter, the role of parents and public awareness. The practical implication is that this research can be piloted in a youth development social home in handling delinquency cases delegated from the Samarinda Class II Child Special Guidance Institute in Tenggarong.